Cardiovascular responses induced by acute video game boxing performance in healthy women - Souza,Luciano Moreira de (2014)
BACKGROUND: Previous studies suggested that some interactive video games induce cardiovascular responses. However, some different styles of video games have not been investigated. OBJECTIVE: We aimed to evaluate cardiovascular responses induced by video game boxing performance in healthy women. METHOD: We evaluated ten female sedentary volunteers, aged 20.9 ± 1.4 years, weight 58.7 ± 8.0 kg, height 163.2 ± 5.4cm. All subjects were weighed and measured. Their heart rate, blood pressure and lactate levels were recorded before and after video game performance. The volunteers played a Sony video game (Nintendo® Wii) by using the boxing method, in which all volunteers played for 10 minutes without interruption. At the end of the game the volunteers were reassessed using the same parameters mentioned above. RESULTS: At the end of the video game boxing performance we observed highly significant increases of lactate production (p < 0.0035) and the double product (heart rate vs. systolic blood pressure) was also higher (p < 0.0001). Both parameters indicate that the performance increased demands of the cardiovascular system. CONCLUSION: We conclude that a ten-minute video game boxing performance induces cardiovascular responses similar to aerobic exercise. This may be a practical form of exercise, but care should be exercised concerning subjects with cardiovascular disorders.